The perception of attachment effect in parents and peers on aggressive behavior in male adolescents - Wibowo, Nurhida Rahmalia; Wimbarti, Supra (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
Interaction among children with their parents and peers has an important role in developing aggression in adolescents. Negative interaction can form children’s negative perception of attachment to their parents and peers. In turn, it facilitates adolescent’s negative schemes from childhood to adolescence. Negative scheme children are generally easy to get anxious, difficult to trust another person in interaction, and aggressive. This study aimed to examine the perceptions of attachment effect to their father, mother, and peer on male adolescents' aggressive behaviors. The subjects of this study were 31 adolescents aged 12-15 years old, who lived in PSMP Antasena in Magelang. They were selected through purposive sampling technique. The data were collected using aggressive behavior scale and modification of parents and peer attachment inventory. The method used for analyzing data was multiple regression. The results of the analysis showed that R=0.688, p<0.01, indicating that the perceptions of father, mother and peer attachment significantly can predict aggression in male adolescents.